A modified capacitance model of RF MEMS shunt switch incorporating fringing field effects of perforated beam. (December 2015) - Guha, Koushik; Kumar, Mithlesh; Agarwal, Saurabh; Baishya, Srimanta
Highlights: Capacitance in MEMS shunt perforated switch including fringing field through holes. Capacitance in up-state and down-state is 25% and 2% respectively of the switch. Error of model value is −4.45% in up-state and −5.78% in down-state condition. Modification of three benchmark models for parallel plate capacitance. Model validity limits range. Abstract: This paper deals with the approach to accurately model the capacitance of non-uniform meander based RF MEMS shunt switch with perforated structure. Here the general analytical model of capacitance is proposed for both up state and down state condition of the switch. The model also accounts for fringing capacitance due to beam thickness and etched holes on the beam. Calculated results are validated with the simulated results of full 3D FEM solver Coventorware in both the conditions of the switch. Variation of Up-state and Down-state capacitances with different dielectric thicknesses and voltages are plotted and error of analytical value is estimated and analyzed. Three benchmark models of parallel plate capacitance are modified for MEMS switch operation and their results are compared with the proposed model. Percentage contribution of fringing capacitance in up-state and down-state is approx. 25% and 2%, respectively, of the total capacitance. The model shows good accuracy with the mean error of −4.45% in up-state and −5.78% in down-state condition for a wide range of parameter variations and −2.13% for ligament efficiency of μ = 0.3.